Milk Alternatives. What Advice should Dental Professionals be Giving?. (2nd May 2021) - Thalukder, Imran; Torofdar, Halima; Collard, Mechelle
Abstract : Drinking milk-like fluids made from plant-based materials, such as soya, nuts and peas, is an increasing trend within the population, and regular consumption of these non-dairy alternatives may increase the risk of developing caries. This article focuses on current research relating to caries risk and consumption of milk-like products, and also investigates the sugar content of milk alternatives available in the UK. CPD/Clinical Relevance: Frequent sugar attacks causes caries. Dentists need to be aware of milk and milk alternatives for some may contribute to the development of caries, and this should form part of their caries risk assessment.